MODEL KOMUNIKASI KESEHATAN DALAM PEMBINAAN GAY DI KOTA PADANG - ., Magfirah; Roem, Elva Ronaning; Zetra, Aidinil (2020)
This research aims to describe how the communication process of the Health Office in gay counseling in Padang city . Researchers also tried to analyze the factors emergence of gay presence reality in Padang City and found a model of health communication conducted by the Padang City Health Office in Gay. The research method used is a Qualitative Approach with data collection techniques through observation, interviews, and FGD techniques. First, the existence and appearance of gays in Padang City are caused by hedonism. Second Communication Model The communication process developed by the Padang City Health Office is carried out by someone who has been appointed as a Counselor. counseling is done from the initial stage through consultation, planning, and persuasive approaches and adjusting the character of each gay so that the communication process can continue as expected by the counselor. Even though the Health Office has not had a significant impact on changing deviant behavior patterns, Gay is trying to receive messages from the counselor, whether he likes it or not about the negative effects of being a man who likes the same sex. In the Message Delivering the Counselor uses the media that is in addition to direct communication face to face indirect communication is also done actively by utilizing the use of social media namely Whatapps as a communication tool between counselor and gay